KONTEMPLASI TUJUAN PENDIDIKAN AKUNTANSI: INTERPRETASI MAKNA BERBAGAI PERSPEKTIF - Yohan Bakhtiar (Universitas Muhammadiyah Jember, 2018)
This study is a contemplation about accounting education objective from various perspective in accounting education research. Qualitative approach with interpretive paradigm are used in this study. The result of this contemplation is various perspective to formulate accounting education objective appropriate with national education objective, UUD 1945, and lesson goal in KKNI. There is only a little difference on redactional aspect however the substance is similar.Keyword: Accounting Education, Objective, Perspective